The initiation of bone formation induced intrinsically by osteoinductive hydroxyapatities - Khoali, Lerato (My University, 2006)
The initiation of new bone formation within the porous spaces of hydroxyapatite (HA) implants involves the expression of osteogenic markers belonging to the TGF-β superfamily. To study the genetic expression of these osteogenic markers in relation to the type of HA implant used and implantation period, five different types of porous HA biomaterials were implanted in the rectus abdominis muscles of adult baboons Papio ursinus, and were harvested at two, three and 12 months. The total RNA of all harvested samples was extracted and analysed using the Northern blot technique. The results showed that Collagen type IV, GDF-10 and BMP-7 were expressed at the early time points at relatively high levels, and their expression levels were significantly reduced at 12 months. The expression of these makers was not affected by the type of porous HA implant used. The histological sections of these specimens at two and three months showed vascularised connective tissue within the porous spaces of the implants with no bone formation. However, at 12 months there were substantial amounts of bone formed in all the studied implants. The down-regulation of the expressed osteogenic markers at 12 months correlates to the amount of bone formed, suggesting some negative feedback mechanism which may be acting via inhibitory Smads proteins in relation to the amount of bone formed. Neither TGF-β1 nor BMP-3 messages were detected in any of the studied samples, It is possible that these bone markers are not expressed locally within the vicinity of the porous HA implants but are adsorbed to the HA implants from the circulatory system.
Faculty of Health Sciences, Degree of Master of Science in Medicine. 9208366a
Keywords: circulatory; hydroxyapatite; bone; system; osteogenic